Evaluation of a recreational team game for seniors: Lifeball - a case study - Holt, A.; Howat, Peter; Alfonso, H. (ACHPER, 2009)
The objective of this project was to assess changes in physical activity, social isolation and loneliness of Lifeball participants as a result of participation in Lifeball. Lifeball is a team game based on walking, ball passing and goal shooting. Newly enrolled Lifeball players (n = 95) aged 50 years and over were recruited from Lifeball clubs in Western Australia. Subjects completed a questionnaire on their physical activity levels and perceptions of their psychosocial health and well-being. The questionnaire was administered at baseline and after 3 months of participation in Lifeball. There was no significant change to overall physical activity levels. However, it appears Lifeball was used to replace other recreational pursuits that the subjects were involved in. There was a positive shift in variables associated with social isolation and loneliness. Lifeball provides alternative physical activity opportunities and may help reduce social isolation and loneliness.